Functions of Artificial Intelligence, Income Investment Instrument, and Crypto Money in Era of The Fourth Revolution - Cicilia Sriliasta; Dewi Sri Surya Wuisan; Tatik Mariyanti (International Transactions on Artificial Intelligence, 2022)
This research examines those related to Artificial Intelligence, stock robotics, and revenue intruments portfolio diversity in the context of the Fourth Industrial Revolution era, artificial intelligence, and concern for the environment. First, our results suggest that a portfolio of these assets is highly dependent, suggesting that large mutual losses are likely to occur during times of disruption in the economy. Second, it supports a large market mood in the near future, indicating that this disruption in the approaching time can increase the market mood of assets, while to support the market mood decreases for a long time.